ASSA14-01-03 Elevation of Matrix Metalloproteinase-9 in the Culprit Coronary Artery Predicts Myocardial No-re flow. (1st December 2014) - Dong, M; Mu, N; Ren, F; Sun, X; Yang, J
Abstract : Background: Matrix metalloproteases (MMPs) have been implicated in the pathogenesis of acute myocardial infarction (AMI). However, little is known about the association between MMP-9 and myocardial no-reflow. The aim of this study was to evaluate the role of MMP-9 at the infarct-related artery as a predictor of no-reflow in patients with ST-elevation AMI. Methods: We prospectively enrolled 90 eligible ST-elevation AMI patients, undergoing successful primary PCI. Blood samples were obtained from the extraction catheter placed distal to the culprit lesion at the beginning of PCI. The levels of MMP-9 were determined in duplicate using the RayBio enzyme-linked immunosorbent assay. Results: No-reflow was observed in twenty-five patients (27.8%). Using multiple logistic regression analysis, local MMP-9 level (OR 3.356, CI: 1.441–16, 881; p = 0.007) were found to be a significant risk factor of no-reflow together with lesion length (OR 6.985, CI: 1.574–18.533; p = 0.009) and thrombus score (OR 5.105, CI: 1.825–25.138; p = 0.041). Conclusions: Elevation of MMP-9 level in the culprit coronary artery may predict no-reflow in patients with ST-elevation AMI underwent PCI.